2020
DOI: 10.4236/ajps.2020.116062
|View full text |Cite
|
Sign up to set email alerts
|

New 5-Alkenyl Resorcinols from <i>Lithraea molleoides</i> (Vell). Eng.

Abstract: Lithraea molleoides (Anacardiaceae) is a tree that grows in South America including Southern Brazil, Southern, and Eastern Bolivia, Southern Paraguay, Northern, and Central Argentina. Infusions, decoctions, or tinctures from its aerial parts (leaves, buds, and young stems) are employed in ethnomedicine mainly against respiratory, and digestive inflammations and illnesses. Antibacterial, antiviral, antioxidant, anti-inflammatory, and antinociceptive activities, among others, have been reported for L. molleoides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Regarding alkyl and alkenyl resorcinols (e.g., 72 and 82), they are characteristic constituents of Anacardiaceae, 97,98 as also are cycloartane-type triterpenes (e.g., 45, 64, and 80; Figure 1h) and xanthones (e.g., 7 and 8; Figure 1f). 99 The three classes of metabolites have been detected in chloroform extracts of propolis of the Indonesian meliponines Heterotrigona itama and Tetragonisca laeviceps and of mango fruits (Mangifera indica).…”
Section: Hypotheses About Plant Origins Of the Constituentsmentioning
confidence: 99%
“…Regarding alkyl and alkenyl resorcinols (e.g., 72 and 82), they are characteristic constituents of Anacardiaceae, 97,98 as also are cycloartane-type triterpenes (e.g., 45, 64, and 80; Figure 1h) and xanthones (e.g., 7 and 8; Figure 1f). 99 The three classes of metabolites have been detected in chloroform extracts of propolis of the Indonesian meliponines Heterotrigona itama and Tetragonisca laeviceps and of mango fruits (Mangifera indica).…”
Section: Hypotheses About Plant Origins Of the Constituentsmentioning
confidence: 99%
“…Dichloromethane extract of L. molleoides was reported to exhibit anti-inflammatory activity and immunostimulant activity on normal lymphocytes [55] and resorcinol 1,3-dihydroxy-5-(tridec-4',7'-dienyl)-benzene was identified as the major constituent and responsible for their biological activities. [56] in their work on isolation, characterization and confirmation of 5-alkenyl resorcinols from dichloromethane extract of L. molleoides using 1H NMR, 13C NMR spectral studies reported the presence of five resorcinols subunit in all of them with different side chains with various degrees of unsaturation.…”
Section: Discussionmentioning
confidence: 99%